Using controlled subsurface releases to investigate the effect of leak variation on above-ground natural gas detection - Mbua, Mercy W., author; Riddick, Stuart N., advisor; Zimmerle, Daniel J., advisor; von Fischer, Joseph, committee member (Colorado State University. Libraries, 2023)
Leaks from underground natural gas (NG) pipelines pose safety and environmental concerns. Pipeline leak detection generally relies on measuring surface methane (CH4) enhancements during walking surveys and/or mobile surveys that attempt to identify CH4 plumes downwind of the pipeline. The likelihood of plume detection is dependent on the above-ground CH4 plume width. The size and shape of the plume is primarily dependent on environmental conditions but could also be complicated by leak characteristics. To investigate the effect of leak characteristics on CH4 plume width, this study uses controlled release experiments to observe above-ground plume width changes with changes in the gas composition, leak rate, and leak depth. Results show that plume width generally decreases with increased NG density, decreased leak rate and increases with depth between 0.6 and 0.9 m, but the above surface plume is undetectable above the background for leaks 1.8 m deep. The study established that the effect of adding heavy hydrocarbons to the NG mixture on plume width is equivalent to the effect of increased leak rate and depth on plume width multiplied by -0.04 and -0.89, respectively, with overall relative uncertainty of -42/ +14 %. This shows that reported leaks in areas with heavier hydrocarbons could currently be missed or underestimated. Further, this study shows that leaks from pipelines laid in covers meeting the Colorado Oil and Gas Conservation Commission minimum depth requirement of 0.9 m could be easier to detect compared to those buried at depths less than the minimum depth. Applying the findings to a real-world scenario, the study illustrates that a successful leak survey protocol tuned to NG leaks from Fayetteville shale (0.66 g/L NG density) may result in missed detections in the Permian, where NG is heavier (1.01 g/L) due to higher percentages of heavy hydrocarbons. Overall, this study illustrates that leak survey protocols for flowlines and gathering lines should be different from distribution pipelines and tailored to the compositions of the transported NG to report emissions accurately.
Keywords: natural gas; subsurface; upstream production; pipeline; flowlines/gathering lines; surveys